Report on the first International Martial Arts and Combat Sports Scientific Society (IMACSSS) Conference - “Game, Drama, Ritual in Martial Arts and Combat Sports” - Vertonghen, Jikkemien (Revista de Artes Marciales Asiáticas, 2012)
The present report provides a brief account of the first conference of the International Martial Arts and Combat Sports Scientific Society (IMACSSS), held in Genova (Italy) on June 8th-10th, 2012. There were 43 oral presentations and 15 posters divided into five themes: (1) Psychological dimensions of martial arts and combat sports (MA&CS); (2) Sociological and historical aspects of MA&CS; (3) Bio physical, bio technical and bio tactical issues in MA&CS; (4) Pedagogy and didactic methodologies in MA&CS; (5) Philosophical aspects, anthropological conceptions and taxonomy in MA&CS. The conference was a well-organised and unique meeting of MA&CS researchers with a wide variety of topics, international presence and expertise. It provided a good opportunity to consolidate and broaden scientific knowledge and research in MA&CS and contributed to the integration of the scientific community involved in their study.